Multivariate Analysis in Sesame (Sesamum indicum L.) - Solanki, Z S; Gupta, Deepak (Annals of Arid Zone, 2016)
Multivariate analysis of divergence among 78 genotypes of sesame for 7 quantitative characters revealed considerable genetic diversity and led to their . grouping into 9 clusters. No relationship between geographic origin and genetic diversity was observed. Capsules per plant contributed maximum, accounting for 3 \.9 of the total divergence. For varietal improvement program in sesame, genotypes like NIC-8388 of cluster II. NIC-84IO of cluster III, GRT-8603 of cluster IV and IC-17477 of cluster VII were important on the basis ofÂ· their genetic distances and higher cluster means.